Research on Parameter Design of Vehicle Braking Resistance and Control Frequency Matching for Subway - CHEN Wenguang; YING Ting; XIE Peijin (Kongzhi Yu Xinxi Jishu)
In order to optimize the parameter design of vehicle braking resistance for the subway, based on the electric braking energy of AC electric drive system and its intermediate voltage control stability, it elaborated the main parameter selection of braking resistance such as power and resistance as well as the matching design of chopping frequency, which provided detailed design thoughts and means for braking resistance and matching of chopping frequency control. Design process was explained in detail through an example. Experimental and application results verify the validity of the proposed method.